Предмет: Математика,
автор: Polina1319
Решите пожалуйста, срочно
Приложения:
Ответы
Автор ответа:
1
x³ - y³ = x² + xy + y²
x³ + y³ = x² - xy + y²
x³ - y³ = (x - y)(x² + xy + y²)
x³ + y³ = (x + y)(x² - xy + y²)
(x - y)(x² + xy + y²) - (x² + xy + y²) = 0
(x + y)(x² - xy + y²) - (x² - xy + y²) = 0
(x - y - 1)(x² + xy + y²) = 0
(x + y - 1)(x² - xy + y²) = 0
x = 0 y = 0
x - y = 1
x + y = 1
2x = 2
x = 1
y = 0
ответ (0, 0) (1, 0)
Похожие вопросы
Предмет: Английский язык,
автор: 130613JIMIN130613
Предмет: Английский язык,
автор: masalskayamari638
Предмет: Физика,
автор: artemsankov2009
Предмет: Математика,
автор: lichikaki333